Metformin Antibacterial Activity on Vaginal Isolates in Polycystic Ovarian Syndrome - Halah Dawood Salman (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Bacterial resistance to antibiotics continues to intensify worldwide, creating an urgent need for adjunct therapies that enhance antimicrobial efficacy. Specific Background: Metformin, a widely used antidiabetic drug, has shown immunomodulatory and antimicrobial properties, yet its effects on vaginal pathogens in women with and without polycystic ovary syndrome (PCOS) remain insufficiently explored. Knowledge Gap: Limited evidence exists regarding whether metformin can potentiate antibiotic activity against common vaginal bacterial isolates, particularly in PCOS patients who often exhibit reduced IL-10 levels and heightened inflammatory states. Aims: This study aimed to evaluate the adjuvant antibacterial effect of metformin when combined with standard antibiotics against Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa isolated from affected women. Results: Metformin enhanced antibiotic inhibition zones notably for K. pneumoniae and P. aeruginosa, while producing a moderate but less consistent synergistic effect on E. coli. Serum IL-10 levels were significantly lower in patients than controls, confirming an underlying inflammatory imbalance. Novelty: This research provides one of the first empirical assessments of metformin’s antibacterial adjuvant role in vaginal infections among PCOS and non-PCOS women. Implications: Findings suggest metformin may serve as a promising supportive agent to strengthen antibiotic efficacy and help mitigate bacterial resistance.Highlight : Metformin enhances the antibacterial effects on K. pneumoniae and P. aeruginosa. IL-10 is lower in PCOS patients, indicating inflammatory imbalance E. coli is the most common bacterium in vaginal infections. Keywords : Metformin, Vaginal Infection, PCOS, Antibacterial Synergy, Antibiotic Resistance